Innovation and dominant design in mobile telephony - Heli Koski; Tobias Kretschmer (The Research Institute of the Finnish Economy (ETLA), 2006)
We document the evolution of product innovation and features in the mobile telephone handset market. We distinguish between two types of product innovation: vertical and horizontal innovation. Using data from 1990 - 2003, we find that some characteristics have subsequently become an industry standard, while some remained as horizontally differentiating features of mobile handsets. We explain this pattern using the concept of dominant design, and results from the theoretical literature on the incentives for horizontal and vertical differentiation.
Keywords: L15; L96; O32; 330; Product innovation; mobile phone handsets; dominant design; min-max principle.; Mobiltelefon; Innovation; Produktdesign